The influence of decompressive craniectomy on the development of hydrocephalus: a review - Jun Ding; Yan Guo; Hengli Tian (Arquivos de Neuro-Psiquiatria)
Decompressive craniectomy (DC) is widely used to treat intracranial hypertension following traumatic brain injury (TBI) or cerebral vascular disease. Many studies have discussed complications of this procedure, and hydrocephalus is a common complication of DC. To further evaluate the relationship between DC and hydrocephalus, a review of the literature was performed. Numerous complications may arise after DC, including contusion or hematoma expansion, epilepsy, herniation of the cortex through a bone defect, CSF leakage through the scalp incision, infection, subdural effusion, hydrocephalus and “syndrome of the trephined”. Several hydrocephalus predictors were identified; these included DC, distance from the midline, hygroma, age, injury severity, subarachnoid or intraventricular hemorrhage, delayed time to craniotomy, repeated operation, and duraplasity. However, results differed among studies. The impact of DC on hydrocephalus remains controversial.